Prescribing of anti-dementia medications in primary care: A retrospective cohort study in 1489 English General Practices - Charlotte Morris; Pearl L. H. Mok; Dame Louise Robinson; Louise Allan; Darren M. Ashcroft; Tom Blakeman; Evangelos Kontopantelis (PLoS ONE, 2026)
Objective Evidence suggests that patient-level characteristics such as socio-economic status or ethnicity affect the likelihood of receiving guideline recommended anti-dementia medications. Existing studies often included all-cause dementia, not just the specific subtypes in which medication is indicated. Patterns of prescribing of Acetyl Cholinesterase Inhibitors (AChEIs) and memantine require further exploration, with little evidence about rates of co-prescribing in English primary care. We examined variations in anti-dementia medication prescribing with patient-level characteristics, and over time. Design and setting Retrospective cohort study, using the Clinical Practice Research Datalink Aurum. Data from 1,489 practices, in England between 2006–2024, were included and linked to patient level Index of Multiple Deprivation data (2019). Cox-regression modelling, clustered at practice level, assessed association between patient-level characteristics and receiving AChEIs, and/or memantine. Time-series analyses examined co-prescribing of memantine and AChEIs. Participants 242,007 patients, aged >=18 years, with Alzheimer’s or Lewy-Body Dementia, or mixed dementia including one of these subtypes, were included. Results Among the 242,007 patients, 63.1% were prescribed an anti-dementia medication; co-prescribing of memantine and AChEIs peaked at 4.2%. Those in the most deprived quintile were less likely to be prescribed AChEIs (Hazard Ratio (HR) 0.82,0.78-0.86) compared to the most affluent quintile. People with Asian (HR 0.89,0.84−96), or Black (HR 0.79, 0.73-0.86) ethnicities were less likely to be prescribed memantine compared to white people. Those with learning disabilities were substantially less likely to be prescribed AChEIs (HR 0.46,0.42-0.50) or memantine (HR 0.58, 0.50-0.67) compared to those without. Conclusion Overall rates of prescribing of anti-dementia medications were lower than expected. Rates of co-prescription of AChEIs and memantine were low, despite guideline recommendations. We found inequity in anti-dementia medication prescribing, relating to multiple patient-level characteristics highlighting the need for more equitable access to evidence-based treatments.